VIDEO A12-4: Derrame pleural - Kasper, Dennis L.; Kritek, Patricia A.; Reilly, John J. (McGraw-Hill's AccessMedicina., 2019)
El video muestra una ecografía torácica, que se realizó para valorar un derrame pleural.